2018
DOI: 10.3390/molecules23092156
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition Stability and Antioxidant Activity of Sour Cherry Liqueurs

Abstract: The aim of the study was to evaluate changes of phenolic and anthocyanin contents, antioxidant activity, aroma compounds and color of sour cherry liqueurs with and without sugar during 6 months of storage at temperatures of 15 °C and 30 °C. Contents of phenolic compounds (HPLC, UPLC-MS) and antiradical activity (ABTS) changes were measured. Color changes were measured by an objective method (ColorQuest XE). During storage fluctuations of phenolic compounds and antioxidant activity content were observed. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Although a decrease in the antioxidant potential is typical for short heat treatments, a retrieval of these properties has been reported during prolonged heat treatment and/or storage. In our case, the observed oscillation in total polyphenol content and ABTS antioxidant activity during 9 months of storage were in line with the results obtained by many others for various products, including fruit liqueurs and diet jams [10,32]. Many studies found that phenolic antioxidants do not follow a specific reaction order.…”
Section: Total Soluble Solids Total Polyphenol Content and Antioxidasupporting
confidence: 92%
See 2 more Smart Citations
“…Although a decrease in the antioxidant potential is typical for short heat treatments, a retrieval of these properties has been reported during prolonged heat treatment and/or storage. In our case, the observed oscillation in total polyphenol content and ABTS antioxidant activity during 9 months of storage were in line with the results obtained by many others for various products, including fruit liqueurs and diet jams [10,32]. Many studies found that phenolic antioxidants do not follow a specific reaction order.…”
Section: Total Soluble Solids Total Polyphenol Content and Antioxidasupporting
confidence: 92%
“…Additionally, the inconsistent trend in antioxidant activity change can be attributed to various reasons, including the hydrolysis of the flavonoid glycosides, delivering an additional -OH moiety that can react with the ABTS cation radical [32]. Moreover, the interaction of the phenolic compounds or their oxidized form with the sugar molecules and the consequent formation of the reduced form of phenolic compounds that can interact with ABTS radicals [35] orto a lesser extent-the presence of non-polyphenol antioxidants can also contribute to the observed lack of correlation between polyphenol content and ABTS radical scavenging activity obtained in our study.…”
Section: Total Soluble Solids Total Polyphenol Content and Antioxidamentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was previously described by Sokół-Łętowska et al [ 39 ]. The HPLC-PDA analysis was performed using a Dionex (Germering, Germany) system equipped with the diode array detector model Ultimate 3000 System (Dionex, Germering, Germany), equiped with quaternary pump LPG-3400A), autosampler EWPS-3000SI and thermostatted column compartment TCC-3000SD, and controlled by Chromeleon v. 7.2 software (Thermo Scientific Dionex, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The details of the compounds are given, together with the specification of the reliability class and references used for the detection Putative identification R t (min) Formula Theoretical m/z Observed m/z Mass error (ppm) Main MS2 fragments MSI reliability class with references used for the annotation Flavanol hexoside 8.79 C 21 H 24 O 11 453.1391 453.1379 −2.78 139.0381 2 106 A-type flavanol dimer I 13.87 C 30 H 24 O 12 577.1341 577.1318 −3.91 245.0434 3 106 Coumaroyl quinic acid 16.00 C 16 H 18 O 8 339.1074 339.1065 −2.91 147.0433–119.0481–91.0534 3 107 109 (epi)afzelechin–(epi)catechin 17.65 C 30 H 26 O 11 563.1548 563.1534 −2.50 107.0480–147.0431–287.0544 2 110 , 111 A-type flavanol trimer I 19.02 C 45 H 36 O 18 865.1974 865.1968 −0.73 245.0441–287.0544–163.0375 3 112 B-type flavanol trimer I 19.02 C 45 H 38 O 18 867.2131 867.2131 0.00 245.0422–127.0379–163.0382 3 106 B-type flavanol tetramer 19.64 C 60 H 50 O 24 …”
Section: Resultsmentioning
confidence: 99%